Evaluación de los estudios sobre la actividad antioxidante de semillas de chenopodium quinoa - Chicoma Cruzado, Néstor Alfredo (2017)
The present work presents a series of studies carried out based on the antioxidant capacity of quinoa seeds, both raw, germinated, in flour, or in bread, and subjected to different controlled processes, and evaluating their increase or decrease in capacity. antioxidant Quinoa stands out in the world of foods for its high nutritional content, in this study its value as a functional food is highlighted, due to its high content of antioxidants. The antioxidant activity of the quinoa seeds was evaluated, measured by the methods: DPPH, ORAC, ABTS, FRAP and discoloration of beta carotene. The results obtained showed greater antioxidant capacity than most pseudocereals, with the exception of buckwheat. Likewise, the antioxidant activity of quinoa seeds, subjected to different processes, such as cooking, washing, spreading, baking and drying, was evaluated; which show highly significant differences between them.